Firm versus Partner Measures of Auditor Industry Expertise and Effects on Auditor Quality - Chi, Hsin-Yi; Chin, Chen-Lung (Auditing : a journal of practice and theory, 2011)
This paper first examines whether the Big 4 audit quality is associated with auditor industry expertise, measured as both individual partner- and audit firm-level leadership. We focus on a sample of listed firms in Taiwan, where audit reports must be audited and signed by the two signing auditors as well as by an audit firm. For accruals analyses, we find that differential discretionary accruals due to industry expertise are driven by a combination of firm and partner expertise. For audit opinion analyses, we find that differential likelihood of a modified audit opinion (hereafter, MAO) is primarily attributable to signing auditor specialists. We also find that firm-level specialists alone are not associated with a higher likelihood of issuing a MAO. However, firm-level specialists, in combination with signing auditor specialists, can add something over and above the effects of the signing auditor specialists alone. Second, we further examine whether there is differential audit quality between signing auditors (i.e., lead and concurring auditors). We find that clients of lead signing auditor specialists, either alone or in conjunction with concurring auditor specialists, have smaller accruals and are more likely to receive a MAO compared to those of nonspecialists. However, concurring auditor specialists alone are not associated with higher audit quality, in terms of either smaller accruals or a higher MAO likelihood. Thus, we conclude that industry expertise is not homogeneous across individual auditors within the same audit firm in Taiwan. Data Availability: Data are available from the sources identified in the text.